Students Self-Regulation: An Analysis of Exploratory Factors of Self-Regulation Scale - Hafnidar Hafnidar; Intan Harniati; Mesfin Hailemariam; Ciptro Handrianto (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
Today academic achievement has become a benchmark of the success of students. Students self-regulation can be measured through self-regulatory instruments that the author has tested in SPSS by looking at the rotation and spread of its components. Self-regulation is important in achieving student’s achievement in study. There are external and internal factors influences the process of students self-regulatory. The aim this study was to created the self-regulatory instruments for students. The reliability value produced by this instrument is quite high which is 0.860. The results of the exploratory analysis produced four constituent components of self-regulation composed in 31 items of scale.